Importance of collaboration of dermatology and rheumatology to advance the field for lupus and dermatomyositis - Victoria P. Werth, MD; Anca D. Askanase, MD; Ingrid E. Lundberg, MD (Wolters Kluwer, 2021)
There have been a number of advances in the clinical and translational understanding of cutaneous lupus and dermatomyositis, which both disproportionately affect women. These advances have involved ongoing collaborations between dermatology and rheumatology that highlight the importance of the skin in these disorders, with improvement in the education of trainees and clinical management of these complex multisystem diseases. In addition, a new disease classification has allowed inclusion of patients with skin-predominant dermatomyositis, frequently associated with systemic findings, in the spectrum of idiopathic inflammatory myopathies. Validated outcome measures allow translational research and facilitate progress toward better and more targeted therapeutics. Clinical trials using disease severity tools, such as the Cutaneous Lupus Erythematosus Area and Severity Index and the Cutaneous Dermatomyositis Disease Area and Severity Index, allow measurement of improvement in the skin. Recent results of phase 2 and 3 trials clearly show that patients will benefit from collaborative interactions and studies between dermatology and rheumatology.